Analysis of very important pharmacogene variants in the Tibetan population from China. (25th February 2021) - Rong, Hao; Dong, Hongzhi; He, Xue; Yuan, Dongya; Bai, Mei; Wang, Li; Liu, Tao; He, Yongjun; Zheng, Jianwen; Wang, Yuhe; Jin, Tianbo
Abstract: Personalized medicine, the treatment best suited for an individual, is a hot field of clinical research in the world. Many recent studies have shown that genetic variations have a great influence on the treatment. This study aimed to identify the distribution differences of very important pharmacogene (VIP) variants between the Tibetan population and the other 26 populations from the 1000 Genomes project. Based on the PharmGKB database, we successfully genotyped 50 VIP variants located in 27 genes in the Tibetan population. We also compared the genotype frequencies of VIP variants between Tibetan population and the other 26 populations. Without adjustment, the Chi‐square test showed that the only significant variant between Tibetans and every other group was rs1801159 in dihydropyrimidine dehydrogenase ( DPYD ), followed by rs1800566 in NAD(P)H quinone dehydrogenase 1 ( NQO1 ) and rs1051296 in solute carrier family 19 member 1 ( SLC19A1 ). After Bonferroni's multiple adjustments, the genotype frequencies distribution of DPYD rs1801159 was found to be different in Tibetans compared to the other 26 groups, apart from ACB and ASW. Moreover, genetic structure/F‐statistics (Fst) analysis and the phylogenetic tree illustrated that Tibetans had a closer affinity with CDX, CHB, CHS, JPT and KHV. Our data will complement pharmacogenomics information of the Tibetan population and provide theoretical support for the realization of individualized medical treatment for Tibetans in the future.